Otolith Growth Rings Pattern of Pristolepis grootii From the Lubuk Siam and Kampar Kanan River, Riau Province - Fadilah, Annisa; Putra, Ridwan Manda; Windarti, Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Lubuk Siam oxbow lake and Kampar Kanan Rivers have different ecosystem characteristics and it may affects the growth pattern of fish living in those river. The growth of the fish, however, can be mirrored in the growth patterns in the otolith. A research aims to understand the pattern of otolith growth rings in the P.grootii captured from both areas was conducted in July to August 2019. Sampling was done 4 times/ month. Otoliths were saved, and the growth ring pattern was observed using a binocular microscope. Results shown that the otolith of fish from the Lubuk Siam lake was 3-4.9 mm length and 0.0132-0.0043 mg weight, while that of the fish from the Kampar Kanan River was 2- 4.3 mm length and 0.0125-0.030 mg weight. The fish from the lake was bigger than fish in the river. However, the fish from the river tend to have more dark rings in the otolith and have heavier otolith than that of the lake’s fish. These data indicate that the fish from the river may grew up slowly and face more growth related problem than the fish from the lake.Keywords: Dark Ring, Otolith, Growth Pattern, Sagita, Pristolepis grootii